Pengaruh Model Problem Based Learning Berbantuan Teka Teki Silang terhadap Hasil Belajar Siswa pada Materi Larutan Elektrolit dan Non Elektrolit - Sarah Christen Ginting; Nurfajriani Nurfajriani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The low learning outcomes of students on electrolyte and non-electrolyte solutions require the application of active and innovative learning models. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by crossword puzzles on student learning outcomes on electrolyte and non-electrolyte solutions for grade XI of senior high school. The study was conducted at SMA Negeri 6 Mandau using a quasi-experimental method and a pretest-posttest control group design. The sample consisted of 70 students divided into two classes, namely class XI IPA 3 as the experimental class and class XI IPA 5 as the control class. The research instrument was a multiple-choice learning outcome test that had been tested for validity, reliability, difficulty level, and discrimination power of the questions. Data were analyzed using the N-Gain test and independent sample t-test. The results showed that the average post-test score of the experimental class was 79.81, higher than the control class at 67.61. The results of the N-Gain test showed an increase in learning outcomes of the experimental class by 0.72 (high category), while the control class was 0.57 (medium category). Based on the hypothesis test using an independent sample t-test, a significance value (sig. < 0.05) was obtained. Therefore, it can be concluded that the crossword puzzle-assisted PBL model has a positive and significant effect on student learning outcomes.